DNA damaging agent-based antibody-drug conjugates for cancer therapy. (30th August 2018) - Fu, Ying; Ho, Mitchell
ABSTRACT: Currently, four antibody-drug conjugates (ADCs) are approved by the Food and Drug Administration or the European Medicine Agency to treat cancer patients. More than 60 ADCs are in clinical development for cancer therapy. More than 60% of ADCs in clinical trials employ microtubule inhibitors as their payloads. A better understanding of payloads other than microtubule inhibitors, especially DNA-damaging agents, is important for further development of ADCs. In this review, we highlight an emerging trend of using DNA-damaging agents as payloads for ADCs. This review summarizes recent advances in our understanding gained from ongoing clinical studies; it will help to define the utility of DNA-damaging payloads for ADCs as cancer therapeutics. Future directions of the development of ADCs are also discussed, focusing on targeting drug resistance and combination treatment with immunotherapy.